Analisis Fitokimia dan Aktivitas Antioksidan Ekstrak Daun Kesambi (Schleira oleosa) Metode DPPH - Holil, Kholifah; Griana, Tias Pramesti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Kesambi (Schleichera oleosa) is one of the forest plants from Indonesia that has potential as medicine. Kesambi has active compounds that act as antioxidants. The purpose of this study was to determine the potential of kesambi leaf as an antioxidant using the DPPH method. Samples of kesambi leaf were extracted in methanol, ethanol, and water solvents by the maceration method. The class of compounds contained in kesambi leaf was tested by the colour reaction test method for alkaloids, flavonoids, triterpenoids, phenols, steroids, saponins, and tannins. Antioxidant activity was tested by the DPPH method to determine IC50 values. Based on the results of the colour reaction test showed that methanol and ethanol solvents were able to bind 6 classes of compounds (alkaloids, flavonoids, triterpenoid, phenols, saponins, and tannins) and water solvents were only able to bind 5 classes of compounds (flavonoids, triterpenoid, phenols, saponins, and tannins) contained in kesambi leaf. The results of antioxidant activity tests using the DPPH method showed the lowest IC50 value was methanol extract (16,12µg/ml) compared to ethanol extract (20,43µg/ml) and water (904,28µg/ml). It was concluded that the leaf extract of kesambi has potential as an antioxidant and which has the best antioxidant ability was extracted in methanol. The class of compounds which were thought to be responsible for the antioxidant activity of the kesambi leaf extract based on the color reaction test were phenols, flavonoids and tannins.Keywords: antioxidant, kesambi, Schleichera oleosa, DPPH